2012
DOI: 10.1021/ef300440w
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Tensions between Reservoir Brine and CO2 at High Pressures for Different Salinity

Abstract: In this paper, an experimental technique has been developed to study the interfacial interactions of the reservoir brine and CO2 system at high pressures and elevated temperatures. Using the axisymmetric drop shape analysis (ADSA) for the pendant drop case, this new technique makes it possible to determine the interfacial tension (IFT) and visualize the interfacial interactions phenomenon between the reservoir brine and CO2 under practical reservoir conditions. The laboratory experiments were conducted for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…After the droplet became stable, the whole system was maintained for about 300 s so that it could reach equilibrium as shown in Figure . This step was used in the determination of the static value of the equilibrium IFT. ,,, An image of the droplet was then captured by the CCD camera and saved in the data acquisition system. Commercial software (DropMeter, MAIST) was used for image analysis and IFT calculation based on eq .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the droplet became stable, the whole system was maintained for about 300 s so that it could reach equilibrium as shown in Figure . This step was used in the determination of the static value of the equilibrium IFT. ,,, An image of the droplet was then captured by the CCD camera and saved in the data acquisition system. Commercial software (DropMeter, MAIST) was used for image analysis and IFT calculation based on eq .…”
Section: Methodsmentioning
confidence: 99%
“…This step was used in the determination of the static value of the equilibrium IFT. 13,15,25,26 An image of the droplet was then captured by the CCD camera and saved in the data acquisition system. Commercial software (DropMeter, MAIST) was used for image analysis and IFT calculation based on eq 5.…”
Section: Experimental Apparatus and Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, CO 2 /water interfacial tensions (γ cw ) can be determined experimentally (many studies reported this data e.g. Arif et al, 2016a;Li et al, 2012;Lun et al, 2012), however, an independent experimental measurement of solid/fluid interfacial tension is not possible because a solid interface is very different from a fluid-fluid interface due to absence of mobility (Li and Neumann, 1992). Consequently, the use of numerical/empirical techniques such as Neumann's equation of state becomes essential (Neumann et al, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…IFT 700 was used for this section of the experiment. This equipment can measure the interfacial tension between liquid-liquid and gas-liquid and high pressure and high-temperature condition using either the pendant drop or rising drop method [27]. In the case of this experiment, the IFT was measured at reservoir temperature conditions 96°C and high pressure (ranging from 200 psi to 2000 psi).…”
Section: Interfacial Tension (Ift) Measurementmentioning
confidence: 99%